Implementation of Project-Based Learning Using The Moodle Platform As An Alternative Learning Method In The Hybrid Life Era - Wahyu Nofiantoro; Heru Nurasa (Aliansi, 2022)
The COVID-19 pandemic forces all aspects of activities to be carried out at home, one of which is in the world of education to suppress the spread of COVID-19. Hybrid life is an inevitable condition, where educational activities are carried out remotely using various information technologies. This study aims to describe qualitatively and quantitatively the design of Project Based Learning lecture activities and their implementation in the office administration study program and the secretariat of the vocational education program, University of Indonesia. The results of this study indicate that the implementation of the online PjBL method uses the Moodle platform was effevtive.  especially in honing students' critical thinking skills and showing good learning outcomes.